Ketidakpastian Layanan Kesehatan Lansia Perempuan Dengan Penyakit Diabetes Melitus Di Dukuh Pancuran - Pardede, Hamonangan; Sanubari, Theresia Pratiwi Elingsetyo; Tauho, Kristiani Desimina (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
The process of aging and old age is a natural process for everyone. Increasing age can put you at risk for diseases that can attack the endocrine system. One of the diseases that many elderly have is Diabetes Mellitus with a total of 1,752 cases in 2018. To help overcome this, a form of elderly health service has emerged that can guarantee and improve health, namely the elderly posyandu. Thus, this study aims to explore the existence of health services for elderly women with Diabetes Mellitus. The method used is descriptive qualitative method with the sample technique used is purposive sampling. The instrument used was an interview guide. The results showed that many elderly women experience Diabetes Mellitus but health insurance such as the elderly posyandu is rarely found in Dukuh Pancuran. The rarity of the posyadu program for the elderly because of the lack of attention from the Dukuh Pancuran administrators can have an impact on the quality of life of the elderly. Therefore, the interaction of the elderly with the social environment is an important factor in maintaining the health needs of the elderly. The conclusion of this research is that health services such as posyandu for the elderly are needed to control and improve the quality of life for the welfare of the elderly. This research can be taken into consideration for administrators of Dukuh Pancuran and Puskesmas in implementing the posyandu program for the elderly.